factorise:a^2+b^2+2bc-c^2
Answers
Answered by
1
a² + b² + 2bc -c²
= a² + b² + bc + bc - c²
= a² + b(b + c) + c(b - c)
nothing further can be done. If there would have been a plus... we could have done it like this..
a² + b(b + c) + c (b + c)
a² + (b + c) (b + c)
a² + (b + c) ²
voila
= a² + b² + bc + bc - c²
= a² + b(b + c) + c(b - c)
nothing further can be done. If there would have been a plus... we could have done it like this..
a² + b(b + c) + c (b + c)
a² + (b + c) (b + c)
a² + (b + c) ²
voila
LishaAngral:
my pleasure
Answered by
2
Hey dear!
Here is yr answer......
=> a²+b²+2bc-c²
=> a²+b²+1bc+1bc-c²
=> a²+b(b+c)+c(b-c)
Hope it hlpz...
Here is yr answer......
=> a²+b²+2bc-c²
=> a²+b²+1bc+1bc-c²
=> a²+b(b+c)+c(b-c)
Hope it hlpz...
Similar questions
Physics,
9 months ago
Social Sciences,
9 months ago
English,
9 months ago
Math,
1 year ago
English,
1 year ago